The role of preoperative serum thyroglobulin in the diagnosis and treatment of differentiated thyroid cancer: a systematic review and meta-analysis - Ying Lu; Hao Zhao; ChunHao Liu; ZiFeng Kuang; XiaoYi Li (Frontiers in Oncology)
BackgroundSerum thyroglobulin (Tg) is a critical marker for monitoring tumor recurrence and metastasis in patients who have undergone total thyroidectomy for differentiated thyroid cancer (DTC). While the definitive role of preoperative serum Tg in DTC is not yet established, studies suggest its importance in differentiating between benign and malignant thyroid nodules with indeterminate cytology, as well as in predicting distant metastasis (DM) in patients with DTC.MethodsA thorough literature review was conducted on the use of preoperative serum Tg in differentiating between benign and malignant thyroid nodules, and in evaluating the extent of DTC lesions. Relevant studies were systematically searched in PubMed, Embase, Cochrane, Scopus, and ClinicalTrials databases. A meta-analysis was performed on studies where the ratios between serum Tg diagnostic thresholds and the upper limit of the reference range were similar.ResultsRecent studies showed significantly elevated preoperative serum Tg levels in patients with DTC compared with normal individuals. However, there are inconsistencies in the serum Tg levels between patients with preoperative DTC and benign thyroid nodules across different studies. In patients with thyroid nodules who had indeterminate cytology (negative Tg antibody), the preoperative serum Tg levels were significantly higher in malignant nodules than in benign ones (meta-analysis: odds ratio: 2.59, 95% confidence intervals: 1.59–4.21, P = 0.0001). Although the meta-analysis indicated that high preoperative serum Tg is a risk factor for central lymph node metastasis in patients with DTC (meta-analysis: odds ratio: 1.68, 95% confidence interval: 1.32–2.14, P < 0.0001), some studies suggest that high preoperative serum Tg in patients with DTC does not necessarily lead to central lymph node metastasis. Furthermore, preoperative serum Tg might possess a suggestive value regarding the likelihood of DTC patients developing DM.ConclusionPreoperative serum Tg shows promise in differentiating between benign and malignant nodules in thyroid nodule patients with indeterminate cytology. However, further research is necessary to determine its predictive significance for lymph node metastasis and DM in patients with DTC.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#searchadvanced, identifier CRD42024472074.